2022
DOI: 10.1039/d1ra08233g
|View full text |Cite
|
Sign up to set email alerts
|

Bright red emission with high color purity from Eu(iii) complexes with π-conjugated polycyclic aromatic ligands and their sensing applications

Abstract: In this review, we summarize the research progress on π-conjugated Eu(iii) luminophores exhibiting bright emission and their physical sensing applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 144 publications
0
16
0
Order By: Relevance
“…The excited‐state equilibrium systems have been demonstrated using the various typed ligands by Parker and Faulkner [13–17] . Recently, we demonstrated that a poly‐aromatic hydrocarbon photosensitizer with a long‐lived T 1 state provides the strong emission in the excited state equilibrium (Figure 1a–b) [18,19] . Herein, we provide a novel method for controlling the T 1 lifetime of photosensitizer units by changing the structure of the ancillary ligand of the complex (Figure 1c).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The excited‐state equilibrium systems have been demonstrated using the various typed ligands by Parker and Faulkner [13–17] . Recently, we demonstrated that a poly‐aromatic hydrocarbon photosensitizer with a long‐lived T 1 state provides the strong emission in the excited state equilibrium (Figure 1a–b) [18,19] . Herein, we provide a novel method for controlling the T 1 lifetime of photosensitizer units by changing the structure of the ancillary ligand of the complex (Figure 1c).…”
Section: Introductionmentioning
confidence: 93%
“…[13][14][15][16][17] Recently, we demonstrated that a poly-aromatic hydrocarbon photosensitizer with a long-lived T 1 state provides the strong emission in the excited state equilibrium (Figure 1a-b). [18,19] Herein, we provide a novel method for controlling the T 1 lifetime of photosensitizer units by changing the structure of the ancillary ligand of the complex (Figure 1c). The present method, which leaves the photosensitizer unmodified, opens up new possibilities for the development of photofunctional materials.…”
Section: Introductionmentioning
confidence: 99%
“…metal-organic frameworks (Ln-MOFs), especially Eu/Tb-MOFs, [23][24][25][26][27][28][29][30][31][32][33][34] have been developed widely for luminescence and detection because the luminescence behaviors of Eu 3+ and Tb 3+ have many advantages due to f-f transitions, such as a relatively fixed emission wavelength, narrow emission peak, larger Stokes shift, etc. However, the absorption peaks of Eu 3+ and Tb 3+ are too narrow to achieve a higher fluorescence quantum yield.…”
Section: Lanthanidementioning
confidence: 99%
“…Much work is devoted to the synthesis of Eu 3+ and Tb 3+ complexes, which are characterized by brilliant luminescence and better emission in the red and green regions respectively. [13][14][15] In comparison with Eu 3+ and Tb 3+ ions, the optical properties of Sm 3+ ions are less studied due to a smaller energy gap between the resonating level ( 4 G 5/2 ) and the subsequent energy state. 5,9,16,17 However, the Sm 3+ ion has some other extraordinary properties such as dual emitting behaviour in UV-visible as well as NIR regions and also emission of various colors (red, orange and green) in a single complex that attract the attention of authors.…”
Section: Introductionmentioning
confidence: 99%